Utilization the Economic Value of Intellectual Property (Copyright) as Collateral Object in Indonesia - Maulida Anggun Nur Rahmi; Aminah (LEGAL BRIEF, 2022)
Intellectual property is the creator's exclusive right, which includes moral rights and economic rights. Economic rights contain economic (commercial) value. Government Regulation Number 24 of 2022 concerning the Creative Economy provides a platform for intellectual property assets to become objects of guarantee for financial institutions, through bank institutions and non-bank financial institutions to maximize their application in business activities. Fiduciary collateral institutions conduct the practice of financing intellectual property asset such as intangible assets as an object of guarantee in bank institutions by utilizing the economic value of intellectual property assets in accordance with the provisions of Article 16 paragraph (3) of Law Number 42 of 1999 concerning Fiduciary collateral, which naturally according the requirements of the object as material rights in accordance with the provisions of Article 499 of the Civil Code. Because of a lack of preparation by several relevant stakeholders, obstacles to the implementation of the use of economic value on intellectual property assets in intangible assets (copyright) have become a problem. In addition to the aspect of legal substance (strictness rule of intellectual property assets as objects of guarantee in each legislation), legal structure (lack of preparation of interested parties, especially the role of appraisal and legal audit service agencies in the valuation of intellectual property intangible assets) and legal culture (legal culture education on the introduction and understanding of intellectual property as an object of guarantee) have not been fully fulfilled. Awareness of each related party as well as regulatory reform through implementing regulations are required to ensure that this policy is implemented successfully.